Regenerasi Tanaman Aren Pada Berbagai Kondisi Ekologis Tempat Tumbuhnya di Areal Garapan Kelompok Tani Hutan Karya Makmur III - Meyzia Ulfa; Indriyanto; Ceng Asmarahman (Jurusan Kehutanan -FHIL-UHO, 2023)
Abstract : Sugar palm plants are one of the non-timber forest products that are widespread throughout Indonesia. This study aims to determine the regeneration of sugar palm and study the ecological conditions where the sugar palm grows in the area cultivated by the Karya Makmur III Forest Farmers Group in Tahura Wan Abdul Rachman. The research method used is the checkered line method with a sampling intensity of 1.5% or as many as 12 measuring plots of a land area of 31.61 ha. The sub-plots were 20 m x 20 m for the old phase, the sub-plots were 10 m x 10 productive for the phase, the sub-plots were 5 m x 5 m for the young phase and the sub-plots were 2 m x 2 m for the seedling and understorey phases. The results showed that the growth rate of sugar palm in the seedling phase (44 individuals/12 plots) was more dominant than the young phases of sugar palm (10 individuals/12 plots), the productive phase (1 individual/12 plots), and the old phase (8 individuals/12 plots). The development of sugar palms in arable areas has generally not been cultivated en masse and farmers still rely on plants that grow naturally. The conclusion in this study is that the sugar palm plants are spread over the growing area with natural rejuvenation as evidenced by the many sugar palm seedlings found around the palm trees and the ecological conditions in the field affect plant sugar plam plants. Keywords : sugar palm plantations, natural regeneration, ecological conditions